A survey on communication method and tool among consultant and contractor in construction project / Mohamad Adib Abdul Talib - Abdul Talib, Mohamad Adib (Faculty of Architecture, Planning and Surveying, 2013)
According to Micheal Hattersbeg (2007), communication is the role used for escort and how coordination in the collection activity or collection of social experts. As an interface, each individual in the collection will have acquired sufficient communication to reach a settlement and the idea sparked something of a problem. This research is about A Survey on Communication Method and Tool among Consultant and Contractor in Construction Project. The aim of this study is to investigate the problem communication between consultant and contractor and the best solution method and tool can be applied on the construction site. Firstly objective to study of the communication process at the construction site. Secondly objective review the methods and tool of communication carried out the construction site. Lastly identify the major problems of communication failure between the consultant to the contractor and otherwise. About 38 questionnaires was distributed to the two locations at the Setapak, Kuala Lumpur about project 70 units of 3 storey housing and Ampang, Kuala Lumpur IB tower project 58 storey . From of the study it was found that there are differences in the methods and tools that prevail between the consultant and the contractor and the appearance of some problems such as poor pronunciation of the two sides is going on in the case study. With this in and that's hope this study will be extended through case studies and examine other that's Problems involve all parties in a construction project in more detail.